Greenhouse Gases from Reservoirs Caused by Biogeochemical Processes - World Bank (World Bank, Washington, DC, 2018)
Reduction of greenhouse gas (GHG) emissions is fundamental to the mitigation of climate change. It has become increasingly important to estimate and report on GHG emissions to enable the implementation of mitigation measures to limit or reduce total emissions. In most cases, such estimation is fairly simple, using known emission factors per surface area or per produced energy unit. However, GHG emissions from reservoirs created for the purpose of electricity generation, water security, or flood protection are very difficult to estimate, and no single emission factor or formula can be applied. The purpose of this note is therefore to provide guidance to World Bank Group (WBG) staff on how to assess GHGs from reservoirs in preparation of dam infrastructure projects. The note discusses: (i) the major biogeochemical processes causing GHG emissions from reservoirs; (ii) the state of current knowledge, and (iii) recommendations for assessing GHG emissions caused by biogeochemical processes for planned reservoirs.